Criticizing the Asset Repatriation Policy for Tax Amnesty in Indonesia: An Interpretive and Comparative Study - Hapsari, Nidya (UI Scholars Hub, 2024)
Indonesia finds tax amnesty as a reliable funding alternative to develop a sustainable economy. Since 1964, Indonesia has implemented five tax amnesty programs. The latest two programs would offer lower amnesty compensation rates if taxpayers repatriated offshore assets back to Indonesia. However, the tax amnesty repatriation policy merely contributed minimal amounts of repatriated assets and low number of participants. Consequently, it failed to raise sufficient liquidity, fiscal revenues, tax compliance and economic growth. Hence, the study aims to (1) determine the justification and mechanism for the asset repatriation policy and (2) criticize the repatriation policy implementation. Applying interpretive and comparative analysis, the study found four reasons why the policy has yet to be optimally implemented. First, the rates for Compensation Money or final income tax on repatriated assets were excessive and did not differ much from those applied on declared offshore assets. Second, selecting strategic sectors entitled to the lowest repatriation rates worsened the government's inconsistency in energy transition policies. Third, inadequate supervision and enforcement of tax law due to lack of an integrated verification system. Finally, the repatriation program had minimum footing from other government agencies responsible for investments in Indonesia, hindering a stable and attractive investment ecosystem.